Youth tackle football head-impact estimation by players and parents: Is the perception the reality? - Schmidt, J. D.; Johnson, R. S.; Lempke, L. B.; Anderson, M.; Le, R. K.; Lynall, R. C. (Journal of Athletic Training, 2023)
Context With growing concerns surrounding exposure to head impacts in youth tackle football, players and parents must understand the exposure level when assenting and consenting to participate.